Pengaruh Kotoran Kerbau Dengan Penambahan Jerami Padi Menggunakan Trichoderma Sp Terhadap Karakteristik Kompos - Irma Suhana; Deno Okalia; Chairil Ezward (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
This research aim to know influence of buffalo dirt with addition of paddy hay use Trichoderma Sp to compost characteristic. This research use Complete Random Device (RAL) Non Factorial 6 treatment level that is : A0 (buffalo dirt 100%), A1 (buffalo dirt 98 + 2% paddy hay), A2 (buffalo dirt 96 + 4% paddy hay), A3 (buffalo dirt 94 + 6% paddy hay), A4 (buffalo dirt 92 + 8% paddy hay), and A5 (buffalo dirt 90 + 10% paddy hay). Data result of perception from each treatment analysed statistically, and if differing reality will be continued with Test Continue Downright Real Difference (BNJ) at level 5 %. Pursuant to research which have can be concluded that buffalo dirt compost with addition of paddy hay use activator of Trichoderma Sp do not have an effect on reality to all perception parameter, but assess highest compost temperature there are at treatment of A4 (buffalo dirt 92 + 8% paddy hay) that is 32,900C, decrease of highest materials there are at treatment of A1 (buffalo dirt 98 + 2% paddy hay) that is 24,00%, and value of pH lowest there are at treatment of A2 (buffalo dirt 96 + 4% paddy hay) that is 7,03. Result of perception of buffalo livestock dirt compost tekstur with addition of paddy hay use Trichoderma Sp bertekstur a little is harsh, black chromatic and soft.